The complete shortwave listener's handbook - Yoder, Andrew R (McGraw-Hill, 1997)
Now shortwave is more fun than ever! Shortwave radio may be the most fun you can have sitting down, and this A-to-Z guide for everyone from absolute beginners to advanced hobbyists is your all-in-one partner in listening. It gives you complete, up-to-date information on equipment, worldwide stations, clubs, satellites, computers, and much more! All you need is enthusiasm to use this book's: Help with choosing and using equipment-from the simplest to the most sophisticated; Guidance on finding hot, newsworthy stations, espionage broadcasts, and pirate and illegal frequencies; Up-to-date listings on stations and frequencies for all inhabited portions of the globe; Insider's guide to web sites with shareware for translating audio Morse code to text, receiver-control demo programs, and much more: Simple, cheap ways to improve reception; Convenient lists of station and equipment dealer addresses; And much more! "Yoder has honed his impressive talent as a writer, making him today one of the hobby's brightest stars."-